Historical Events as a Means of Iconographic Interpretation: The Reconstruction of Lost Greek Historical Paintings of the Fifth and Fourth Centuries B.C. - Painesi, Anastasia (Cahiers d'histoire)

(untitled) (Cahiers d'histoire, 2012)
The disappearance of Greek monumental painting causes fundamental problems in the study of this particular form of art. Texts referring to or works of art inspired by Greek paintings seem to be frequently inadequate at the task of providing a realistic reconstruction of the painted works. Nevertheless, the reconstruction of the date and type of representation of historical paintings seems to be facilitated by texts of historical context that offer valuable informations on the events that inspired the painters of the fifth and fourth Centuries B.C. This paper will examine specific cases of Classical paintings, such as the Battle of Marathon and the Battle of Mantineia, whose iconographical reconstruction depends considerably on historiographical testimonies.